Kinetic Studies on the Polymerization of Some Vinyl Monomers by Mn(III)-Tartaric Acid Redox System - RAJENDIRAN, T.V.; SUBBU, S. (Asian Journal of Chemistry, 2010)
Kinetic studies on the polymerization of methylacrylate and acrylamide initiated by the redox system Mn(III)-tartaric acid have been carried out in aqueous sulphuric acid medium at 15ºC. The effects of [monomer], [Mn (III)], [tartaric acid], [H+] and ionic strength on the rates of polymerization and Mn(III) ion disappearance have been studied. A mechanism consistent with the experimental observations has been suggested. The rate parameters ki/ko and kp/kt have been calculated and correlated to monomer and polymer radical reactivities, respectively. Methyl acrylate has been found to have higher monomer and polymer radical reactivities than acrylamide.